2019
DOI: 10.1111/jce.14122
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary vein isolation using a higher power shorter duration CLOSE protocol with a surround flow ablation catheter

Abstract: Introduction The CLOSE protocol combines ablation index (AI) and ≤6 mm interlesion distance using standard power settings for the treatment of atrial fibrillation (AF). The purpose was to compare the safety and efficacy of a conventional CLOSE and a higher power shorter duration (HPSD)‐CLOSE pulmonary vein isolation (PVI) strategy. Methods and Results All consecutive patients referred for PVI were included after informed consent was obtained from them. Group 1 was treated with a standard CLOSE protocol and gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
88
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(101 citation statements)
references
References 13 publications
(21 reference statements)
12
88
1
Order By: Relevance
“…This hypothesis was supported by some clinical trials. Bertaglia et al reported a RCT study between SFc and TCc, and observed a similar 6 months follow‐up success rate between for both groups, which finding was in line with Park et al The possible mechanism might have involved an observation of no significant differences in regard to RF power delivery or lesion size between SFc and TCc . Therefore, both STSFc and STc share CF‐sensing technology, which results in similarly long‐term success rates between two groups.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…This hypothesis was supported by some clinical trials. Bertaglia et al reported a RCT study between SFc and TCc, and observed a similar 6 months follow‐up success rate between for both groups, which finding was in line with Park et al The possible mechanism might have involved an observation of no significant differences in regard to RF power delivery or lesion size between SFc and TCc . Therefore, both STSFc and STc share CF‐sensing technology, which results in similarly long‐term success rates between two groups.…”
Section: Discussionsupporting
confidence: 60%
“…Bertaglia et al reported a RCT study between SFc and TCc, and observed a similar 6 months follow-up success rate between for both groups, which finding was in line with Park et al 6,9 The possible mechanism might have involved an observation of no significant differences in regard to RF power delivery or lesion size between SFc and TCc. 30 to excessive fluid delivery during the procedure. The STSFc procedure uses more homogeneous cooling of the whole tip, so less irrigation fluid is needed.…”
Section: Discussionmentioning
confidence: 99%
“…However, no cardiac tamponade or atrio-esophageal fistulas or PV stenoses were noted in study. 11 Berte, et al 12 ≥450 at the roof and inferior regions). Esophageal temperature monitoring was standard-of-care.…”
Section: Validation Of Hpsd Rfa In Humansmentioning
confidence: 98%
“…Berte, et al in this issue of the JCE, have carried out an elegant single‐center nonrandomized study comparing two different strategies of RF energy application for PVI using the CLOSE protocol in patients with paroxysmal AF (80%) and persistent AF (20%). They have tested the efficacy and safety of a “high‐power short duration (HPSD)” RF energy application compared to the conventional power settings.…”
Section: Validation Of Hpsd Rfa In Humansmentioning
confidence: 99%
See 1 more Smart Citation